The efficient management of the order cycle supply chain. Proposal and application to case of a Colombian SMEs (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
Trying to reach times control, traditionally the order cycle analysis has been done over the paradigms of the production engineering. However, there are new ways for this understanding. This article present a methodology to review the times involvedin the lead time, considering as a framework the supply chain management concept that proposes all the activities in a process like the collection of two basic flows:information and product. Moreover, this proposal is applied to the case of a Colombiansmall-sized company.
Keywords: Order cycle; times; value chain; supply chain (SC); information flow; product flow.